Outcome characteristics of surgical management of single-level junctional thoracolumbar fractures by short segment posterior transpedicular fixation in selected patients - Sajad Hussain Arif; Khurram Khan; Mohsin Fayaz; Abrar Ahad Wani; Sarabjit Singh Chibber; Nayil Khursheed Malik; Zulfikar Ali (Journal of Craniovertebral Junction and Spine)
Introduction: The susceptibility of the thoracolumbar junction to injury is attributed mainly to the transition from a relatively rigid thoracic kyphosis to a more mobile lumbar lordosis that occurs at thoracic T11 to lumbar L2 level. Materials and Methods: We present our experience of management of 87 patients of single-level injury who presented with or without neurological deficit between March 2014 and October 2018. All adult patients (18–59 years) were included who were selected for management by single-level posterior transpedicular fixation and followed up for a minimum of 12 months. Results: The male-to-female ratio in our study was 6.3:1 with a mean age of 32 years. Forty-eight percent were in the work-productive age group of 31–40 years. The L1 vertebra was the most commonly fractured (47%) followed by D12, L2, and D11 vertebra, respectively. Thoracolumbar injury classification severity score 6 was the most common score at presentation. More than 80% patients had some degree of neurological deficit on American Spinal Injuries Association grading with Grade C being the most common pattern of presentation of spinal cord neurological deficit. About 25% patients had some degree of neurological improvement at 12 months follow-up. Among them, 10% achieved an ambulatory status from a bed-ridden status signifying the importance of surgical management in appropriately selected patients. Conclusions: Single-level transpedicular fixation can be offered to a group of selected patients for rehabilitative purposes. This is the largest study discussing only junctional thoracolumbar injuries and also outcomes in single-level posterior instrumentation.